Continuing Engineering Education : Why and How ? - Saluja, H. L. (Journal of Engineering Education Transformations, 1989)
The present paper to begin with attempts to explain the concept of continuing engineering education as applied to technical and professional manpower development. It then establishes the need for such an education in view of changing/emerging technologies. The different modes of delivery of continuing education programmes are then discussed emphasizing the need for this form of education for removal of obsolescence and staying upto date.